PENGARUH KOMBINASI MEDIA TANAM TERHADAP SIFAT FISIK TANAH DAN PERAKARAN BEBERAPA MACAM BIBIT PORANG (Amorphophallus oncophyllus Prain) - Seruni Atyra Kinanti; Purwadi; Bakti Wisnu Widjajani (BPFP Universitas Bengkulu, 2023)
[PHYSICO-CHEMICAL CHARACTERISTICS OF SOIL-COMPOST MIXTURES AS ROOTING MEDIA FOR ELEPHANT FOOT YAM (Amorphophallus oncophyllus Prain)]. Tuber crops such as elephant foot yam have specific demands on the structure of growing media especially in terms of their physical and chemical characters due to the small rooting volume. Therefore, the objective of this study was to determine the interactive effects of seed materials and different proportions of soil-compost mixtures on their physico-chemical properties and root growth of elephant foot yam. This pot trial was conducted from July 2022 to March 2023 in coffee and sengon plantation located in Sumberejo Village, Purwosari, Pasuruan, East Java. Treatments were arranged in a factorial scheme using a Completely Randomized Design (CRD) with two factors and three repetitions. The factors included three types of seed materials, i.e., true seed, tuber, and bulbil for the first factor and five different proportions of soil-compost mixtures (w/w), i.e., 100% soil, 66.7% soil+33.3% compost, 50% soil+50% compost, 33.3% soil+66.7% compost, and 100% compost. Results showed that the interactive effects of the two treatments on the observed variables were not significantly different (p>0.05). Treatment of mixture of 2 kg soil and 4 kg compost (33.3% soil+66.7% compost) produced clayey soil texture with 1.12 g/cm3 for bulk density, 2.26 g/cm3 for specific gravity, 59.34% for soil porosity, and 38,55% for moisture content at field capacity. The bulbil type seed produced a better root growth than the other seeds